IFN-γ derived from activated human CD4+ T cells inhibits the replication of SARS-CoV-2 depending on cell-type and viral strain - Jun Shimizu; Tadahiro Sasaki; Guang Han Ong; Ritsuko Koketsu; Yoshihiro Samune; Emi E. Nakayama; Tetsuharu Nagamoto; Yuki Yamamoto; Kazuo Miyazaki; Tatsuo Shioda (Scientific Reports)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and vaccination elicit both T cell and B cell immune responses in immunocompetent individuals. However, the mechanisms underlying the antiviral effects mediated by CD4+ T cells are not fully understood. In this study, we analyzed the culture supernatant (SN) from polyclonally stimulated human CD4+ T cells as a model for soluble mediators derived from SARS-CoV-2-stimulated CD4+ T cells. Interestingly, this SN inhibited SARS-CoV-2 propagation in a viral strain- and host cell type-dependent manner. The original wild-type showed the highest susceptibility, whereas the Delta variant exhibited resistance in the human monocyte cell line. In addition, antibody-dependent enhancement (ADE) of infection with the original strain was also abolished in the presence of the SN. The findings showed that the inhibitory effect on viral propagation by the SN was mostly attributed to interferon-γ (IFN-γ) that was present in the SN. These results highlight the potential role of IFN-γ as an anti-SARS-CoV-2 mediator derived from CD4+ T cells, and suggest that we need to understand the SARS-CoV-2 strain-dependent sensitivity to IFN-γ in controlling clinical outcomes. In addition, characterization of new SARS-CoV-2 variants in terms of IFN-γ-sensitivity will have important implications for selecting therapeutic strategies.